2018
DOI: 10.1002/ejp.1305
|View full text |Cite
|
Sign up to set email alerts
|

The Adjective Rating Scale for Withdrawal: Validation of its ability to assess severity of prescription opioid misuse

Abstract: Findings supported the reliability and validity of the ARSW to assess withdrawal of prescription opioids in individuals with chronic noncancer pain. The instrument can be applied indistinctly in men and women. An increase in the ARSW scores could be used as an indicator of potential risk of prescription opioid-use disorder during long-term treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Withdrawal symptoms can include patient discomfort, autonomic changes (hypertension, tachycardia), joint and muscle aches/pain, gastrointestinal cramping, lacrimation, rhinorrhea, tremors, emesis, and drug cravings. 14 Managing withdrawal symptoms is important and patients who undergo severe withdrawals are able to have their symptoms treated with an alpha 2 agonist such as clonidine or lofexidine. These agonist medications reduce NA-ergic activity by binding to alpha-2 auto-receptors on these NA neurons, leading to feedback inhibition of the NA neurons' mimicking the previous opioid-induced inhibition.…”
Section: Medication Assisted Treatmentsmentioning
confidence: 99%
“…Withdrawal symptoms can include patient discomfort, autonomic changes (hypertension, tachycardia), joint and muscle aches/pain, gastrointestinal cramping, lacrimation, rhinorrhea, tremors, emesis, and drug cravings. 14 Managing withdrawal symptoms is important and patients who undergo severe withdrawals are able to have their symptoms treated with an alpha 2 agonist such as clonidine or lofexidine. These agonist medications reduce NA-ergic activity by binding to alpha-2 auto-receptors on these NA neurons, leading to feedback inhibition of the NA neurons' mimicking the previous opioid-induced inhibition.…”
Section: Medication Assisted Treatmentsmentioning
confidence: 99%
“…Withdrawal symptoms appeared either in the context of discontinuation or dose reduction and were encountered in patients abusing tramadol and those with therapeutic doses. It has recently been suggested that an increase in withdrawal intensity during opioid treatment in chronic pain could be used to identify patients at risk of developing a prescription opioid use disorder 36,37 . Typical and atypical opioid signs of tramadol withdrawal have been observed 38 …”
Section: Discussionmentioning
confidence: 99%
“…This study highlights the role of tramadol use for stimulant and/or opioid psychoactive effects (well-being, euphoria, anxiolysis, hypnotic and forgetting problems) as a driving factor for primary SUD in withdrawal intensity during opioid treatment in chronic pain could be used to identify patients at risk of developing a prescription opioid use disorder. 36,37 Typical and atypical opioid signs of tramadol withdrawal have been observed. 38 Interdependence between mood, opioid tolerance/dependence, and pain plays a crucial role in the difficult reversibility of dependence on opioid pain treatment.…”
Section: Reports Of High-risk Tramadol Use To the French Addictovigil...mentioning
confidence: 99%
“…Participants also met a minimal threshold of sleep, pain, and withdrawal symptoms as a screening requirement for the larger study. Specifically, eligibility screenings required scoring ≥4 on a 0-10 numeric pain intensity scale, having above-average (≥50) score on at least one scale for sleep disturbance and sleep-related impairment using the Patient-Reported Outcomes Measurement Information System (PROMIS; Yu et al, 2011), and reporting within "moderate" range on 25% of self-reported withdrawal signs using the Adjective Rating Scale for Withdrawal (Coloma-Carmona et al, 2019). We specifically recruited adults displaying moderate symptom burden to meet the aims of the larger study that tested an intervention to reduce withdrawal symptoms.…”
Section: Participantsmentioning
confidence: 99%